2017
DOI: 10.2136/vzj2016.09.0077
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Dissolved Organic Carbon and Nitrate in Waters of a Forested Catchment Using Wavelet Analysis

Abstract: Understanding natural controls on N and C biogeochemical cycles is important to estimate human impacts on these cycles. This study examined the spatiotemporal relationships between time series of weekly monitored stream and groundwater N and C (assessed by NO 3 − and dissolved organic C [DOC]) in the forested Wüstebach catchment (Germany). In addition to traditional correlation analysis, we applied wavelet transform coherence (WTC) analysis to study variations in the correlation and lag time between the N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 72 publications
1
36
0
Order By: Relevance
“…Because of the diversity of landforms and geology covered, we believe these groundwater C values are likely substantially similar to the concentrations and distribution beneath other continents. Measurements of groundwater DOC (e.g., Huang et al 2015, Thayalakumaran et al 2015, Weigand et al 2017 and DIC (e.g., Chaillou et al 2014, Samanta et al 2015, Cao et al 2016) under other countries and continents, although rare, are in the same ranges as those in our survey. We determined the average C content at various depths by smoothing the depth versus groundwater age relationship using locally weighted sequential smoothing (Cleveland 1979) as described earlier.…”
Section: Introductionsupporting
confidence: 68%
“…Because of the diversity of landforms and geology covered, we believe these groundwater C values are likely substantially similar to the concentrations and distribution beneath other continents. Measurements of groundwater DOC (e.g., Huang et al 2015, Thayalakumaran et al 2015, Weigand et al 2017 and DIC (e.g., Chaillou et al 2014, Samanta et al 2015, Cao et al 2016) under other countries and continents, although rare, are in the same ranges as those in our survey. We determined the average C content at various depths by smoothing the depth versus groundwater age relationship using locally weighted sequential smoothing (Cleveland 1979) as described earlier.…”
Section: Introductionsupporting
confidence: 68%
“…Conventional approaches to resolving aquatic transport problems are based on assessments of hydrochemical observations in the time domain. However, novel approaches transforming the problem into the frequency domain have emerged, allowing to analyze temporal patterns (Crawford et al, 2017;Kirchner & Neal, 2013;Schmidt et al, 2018;Weigand et al, 2017;Yan et al, 2017) and provide quantitative estimates of transport rates (Godsey et al, 2010;Guan et al, 2011;Riml & Wörman, 2015) as functions of the inherent time scales of the observed dynamics. The Fourier representation is a way to complement time domain analyses that unlocks new possibilities to utilize high-frequency hydrochemical observations.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon stored in soil and plant residues is receiving considerable interest, because they present a long term carbon sink that can be affected by climate and land use change [57]. This, in turn, can affect the transport of Dissolved Organic Carbon (DOC) through the vadose zone (e.g., [58]). Clearly, the transport of DOC is closely linked to its transit time as it reflects the potential of soils to buffer DOC [59,60].…”
Section: Implications Of the Presented Resultsmentioning
confidence: 99%